Колекція тропічних та субтропічних рослин криворізького ботанічного саду – основа для фітодизайну інтер’єрів Кривбасу - Boyko, L.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2003)
The analysis of collection fund of tropical and subtropical plants in Kriviy Rig botanical gardens of the NAS of Ukraine (KBG) is carried out. The peculiarities of introduction in conditions of KBG are determined. On the basis of researches of ecological and biological peculiarities of introducents is extended the assortment of plants for phytodesign in Krivbass.